S121 Cell tracking in lung cancer. (15th November 2017) - Patrick, SP; Kolluri, K; Davies, AV; Sage, EK; Lythgoe, M; Edwards, A; Kalber, TL; Janes, SM
Abstract : Introduction: Lung cancer is the leading cause of cancer death worldwide with over 70% of patients presenting with incurable disease and few effective treatments. We previously demonstrated that mesenchymal stem cells transduced to express TNF-related apoptosis inducing ligand (TRAIL), will home to and induce apoptosis of tumour cells in vitro and reduce tumour growth in multiple in vivo models. A key unknown of cellular therapy is the location and duration of cells following intravenous delivery. 111 Indium-oxine is established for lymphocyte tracking but it has low sensitivity and is toxic to cells. 89 Zirconium-oxine is a novel PET tracer which has better sensitivity and lower toxicity. Our study aimed to label MSCTRAIL with 89 Zr with the aim of tracking cells in patients enrolled in the TACTICAL trial – an early phase trial delivering MSCTRAIL to patients with metastatic lung adenocarcinoma. Methods: MSC-TRAIL cells were incubated with multiple doses of 89 Zr-oxine and label retention measured using a gamma counter. Cells were assessed for cell viability using cell proliferation assays, TRAIL expression was determined using flow cytometry and ELISA and apoptosis was determined using co-culture experiments with luciferase expressing cancer cell lines and bioluminescent readout. DNA damage and cellular stress was assessed using western blotting. To determine whether radiolabelled cells could be detected in vivo, 2 × 10 5 89  Zr-Oxine MSC-TRAIL cells were delivered intravenously and imaging was performed at multiple time points (Mediso PET-CT, AMI-X). Results: 89 Zr-oxine labelling at clinically relevant doses did not affect cell proliferation and therapeutic efficacy was maintained in co-culture experiments. There was no evidence of DNA damage and cell stress response and cellular phenotype was maintained. CT/PET imaging after labelling and delivery of the cells into mice showed good correlation with bioluminescent signal confirming its use a high sensitivity tracking tool. Conclusion: 89 Zr-oxine can be used to successfully radiolabel genetically modified stem cells without effecting cell viability or therapeutic efficacy. We are currently performing in vivo studies to enable further translation into a clinical trial and will ultimately track MSC-TRAIL after patient administration via radiolabelling with 89 Zr-oxine.